The Influence of Work Conflict, Work Stress, and Work Motivation on Employee Performance at Jiwa Muda Organizer - Hanun Aufa Nur Khosyi; Sonja Andarini (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of work conflict, work stress, and work motivation on employee performance at Jiwa Muda Organizer. In the dynamic wedding organizer industry, work conflict and stress often arise due to high job demands and interactions with various stakeholders. Therefore, this study seeks to measure how these factors influence employee performance, both partially and simultaneously. The research method used is quantitative, with a multiple linear regression approach. Data were collected through questionnaires distributed to both permanent and freelance employees at Jiwa Muda Organizer. The results indicate that work conflict and work stress negatively affect employee performance, while work motivation has a positive effect. Simultaneously, these three variables significantly influence employee performance. These findings highlight that effective management of work conflict and stress, as well as increased motivation, can enhance productivity and work efficiency at Jiwa Muda Organizer.